(untitled) (Bioagro, 2020)
Deficit irrigation is an alternative that allows the rational use of water applied with minimal impact on production. The objective was to evaluate the effect of deficit irrigation on the yield of coriander (Coriandrum sativum L.) sown in monoculture (CM) and in association (A) with chives (Allium fistulosum L.) (CAC). The experimental design was completely randomized with five repetitions in 2x4 factorial arrangement of the treatments. Four irrigation sheets (I) were applied: 100, 80, 60 and 40 % of the substrate water retention. Fifty days after sowing, the height of the bunch in coriander and of the tiller in chives (HB, HT), length of root (LR), number of plants per bunch (NPB), bulbils per tiller (NBT) and leaves per plant (NLP); and in each bunch and tiller: aerial dry biomass (ADB), roots, surface and total dry biomass (RDB, SDB, TDB); and root-aerial part ratio dry biomass (RARDB), were evaluated. The analysis showed significant differences on the variables studied, except NBT and RARDB in chives. In coriander, NPB depended on I; RDB on A; LR, NLP and NLB on Lr or A; while HB, ADB, SDB, and RARDB on the interaction of I with A. HB was greater in CM+Lr=100 %; ADB, SDB greater in CM+ Lr≥60 %. In CAC, chives reached greater HT, NLP, ADB, SDB and RDB with Lr≥80 %. It is concluded that CM with Lr=100 % and CAC with Lr³80 % were the best treatments, allowing greater plant height and yield.